2019
DOI: 10.1002/jaba.622
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of accumulated and distributed reinforcement periods with children exhibiting escape‐maintained problem behavior

Abstract: Differential reinforcement is a common treatment for escape-maintained problem behavior in which compliance is reinforced on a fixed-ratio (FR) 1 schedule with brief access to positive and/or negative reinforcement. Recent research suggests some individuals prefer to complete longer work requirements culminating in prolonged (i.e. accumulated) reinforcement periods relative to brief (i.e. distributed) periods, but prolonged work exposure may evoke problem behavior and prevent compliance from contacting reinfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
27
1
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(34 citation statements)
references
References 20 publications
3
27
1
3
Order By: Relevance
“…DeLeon et al (2014) described this as a distributed reinforcement arrangement. This arrangement may lessen the aversiveness of the instructional context by keeping exposure to instruction brief and by ensuring frequent reinforcement of compliance (e.g., Fulton et al, 2020). The small magnitude of reinforcement may also prevent or delay satiation to the reinforcer for compliance.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…DeLeon et al (2014) described this as a distributed reinforcement arrangement. This arrangement may lessen the aversiveness of the instructional context by keeping exposure to instruction brief and by ensuring frequent reinforcement of compliance (e.g., Fulton et al, 2020). The small magnitude of reinforcement may also prevent or delay satiation to the reinforcer for compliance.…”
mentioning
confidence: 99%
“…Research has suggested several practical advantages associated with arranging accumulated reinforcement, such as increased task-completion rates, shorter overall task durations (Bukala et al, 2015;DeLeon et al, 2014), more rapid skill acquisition (e.g., Frank-Crawford et al, 2019;Kocher et al, 2015), and decreased problem behavior (e.g., Fulton et al, 2020;Robinson & St. Peter, 2019). Further, when provided a choice between accumulated and distributed reinforcement contingencies, many individuals have demonstrated a preference for accumulated reinforcement arrangements (e.g., Bukala et al, 2015;DeLeon et al, 2014), including individuals with escape-maintained problem behavior (e.g., Fulton et al, 2020). Robinson and St. Peter (2019) compared task completion and problem behavior under accumulated and distributed reinforcement arranged using fixed-ratio (FR) 1 schedules.…”
mentioning
confidence: 99%
“…Mask Preference Assessment. For Roman, experimenters completed a concurrent chains preference assessment (see Fulton et al, 2020) for mask type before each experimental session following forced-exposure sessions during the initial baseline phase. For all experimental sessions, the experimenter initiated the session by presenting both mask types (loop mask or tie mask) on the table in front of Roman and saying, "Pick one."…”
Section: Preference Assessmentsmentioning
confidence: 99%
“…Thus, the current study also included brief consumption periods (30 s) relative to prior studies. For example, Hanley et al (2005), Heal and Hanley (2007), and Fulton et al (2020) arranged 120-s, 180-s, and 600-s consumption periods, respectively. Experimenters equated consumption periods across both paired-item and multiple-stimulus assessment sessions in the current study.…”
Section: Paired Stimulus Mean Trials To Completionmentioning
confidence: 99%
“…These initial-link stimuli can then be presented in a manner similar to those of more traditional preference assessments, in which an approach response to the initial-link stimulus results in a reinforcer-consumption period (e.g., after selecting the image of playing basketball, the individual could then play basketball for a period of time). This approach has been used to assess individuals' preferences for behavioral interventions (Fulton et al, 2020;Luczynski and Hanley, 2010;Tiger, Hanley, & Heal, 2006) and teaching strategies (Halbur et al, 2020;Heal et al, 2009;Slocum & Tiger, 2011), among other complex events (Tiger, Hanley, & Hernandez, 2006).…”
mentioning
confidence: 99%